The role of adsorbed ions during electrocatalysis in ionic liquids - Ejigu, Andinet; Walsh, Darren A. (American Chemical Society, 2014)
The effects of electrode–adsorbate interactions on electrocatalysis at Pt in ionic liquids are described. The ionic liquids are diethylmethylammonium trifluoromethanesulfonate, [dema][TfO], dimethylethylammonium trifluoromethanesulfonate, [dmea][TfO], and diethylmethylammonium bis(trifluoromethanesulfonyl)imide, [dema][Tf2N]. Electrochemical analysis indicates that a monolayer of hydrogen adsorbs onto Pt during potential cycling in [dema][[TfO] and [dmea][TfO]. In addition, a prepeak is observed at lower potentials than that of the main oxidation peak during CO oxidation in the [TfO]−-based liquids. In contrast, hydrogen does not adsorb onto Pt during potential cycling in [dema][Tf2N] and no prepeak is observed during CO oxidation. By displacing adsorbed ions on Pt surfaces with CO at a range of potentials, and measuring the charge passed during ion displacement, the potentials of zero total charge of Pt in [dema][TfO] and [dmea][TfO] were measured as 271 ± 9 and 289 ± 10 mV vs RHE, respectively. CO displacement experiments also indicate that the [Tf2N]− ion is bound to the Pt surface at potentials above −0.2 V and the implications of ion adsorption on electrocatalysis of the CO oxidation reaction and O2 reduction reaction in the protic ionic liquids are discussed.